ANALYSIS OF DRIVERS AND CHALLENGES IN CIRCULAR ECONOMY WITH SWARA AND BWM METHODS IN CLOTHING SECTOR - Ezgi Demir; Özüm Eğilmez; Çağlar Karamaşa; Halil Gökcan; Gözde Koca (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
The circular economy is a sustainability model that reduces environmental impacts and enables products to be recycled effectively. In this respect, the clothing sector is one of the sectors that has the highest environmental impact in the circular economy system. In this study, drivers and challenges of circular economy in clothing sector were analyzed with SWARA and BWM methods. The results show that the SWARA and BWM methods are quite similar and can be used by decision makers. In both methods, " Cost savings from conservation in resources" as the driver of the circular economy and "lack of training and knowledge" as a challenge took the first row. This study shows the lack of awareness and legitimacy for the institutionalization of the circular economy approach in the clothing industry in Turkey, will be useful in other developing and transition economies and improve the functioning of vision is considered.